2000
DOI: 10.1182/blood.v96.4.1239.h8001239_1239_1246
|View full text |Cite
|
Sign up to set email alerts
|

Nonmyeloablative stem cell transplantation for congenital immunodeficiencies

Abstract: The optimal approach for stem cell transplantation in children with immunodeficiency has yet to be determined. Conditioning therapy is necessary for reliable engraftment and full immune reconstitution; however, the beneficial effect of cytoreductive conditioning is counterbalanced by increased short- and long-term treatment-related toxicity. Whether bone marrow transplantation with a nonmyeloablative preparative regimen was sufficient for the establishment of donor immune reconstitution, with the resultant cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
19
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 12 publications
2
19
0
Order By: Relevance
“…Similar observations have also been made in patients with FHLH who have undergone HSCTs, in whom even low numbers of normal leukocytes were sufficient to control the abnormal activation of macrophages and lymphocytes (12,16). Hence, reports have suggested that full myeloablative conditioning might not be necessary (9,17), particularly in patients with preexisting comorbidities, as the use of reduced-intensity conditioning in CHS may be a potential way to reduce the high transplantation-related mortality (18). It also provides rapid engraftment and reduces shortand long-term toxicity, thus offering acute survival advantage.…”
Section: Discussionsupporting
confidence: 60%
“…Similar observations have also been made in patients with FHLH who have undergone HSCTs, in whom even low numbers of normal leukocytes were sufficient to control the abnormal activation of macrophages and lymphocytes (12,16). Hence, reports have suggested that full myeloablative conditioning might not be necessary (9,17), particularly in patients with preexisting comorbidities, as the use of reduced-intensity conditioning in CHS may be a potential way to reduce the high transplantation-related mortality (18). It also provides rapid engraftment and reduces shortand long-term toxicity, thus offering acute survival advantage.…”
Section: Discussionsupporting
confidence: 60%
“…A MEDLINE literature review from 1993 to 2013 was conducted. A total of 21 papers were identified (Table S1), with 20 written in English (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)36) and one written in Dutch (30). The majority of publications were case reports, along with a few single-center studies (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Stem cell transplant therapy was therefore recently tested as a potential to cure for this disease (14,15), but only a few single-center studies have been published (16)(17)(18). In addition, a European survey was published approximately a decade ago (19), but the available publications are otherwise limited to case reports (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). This report represent a single-center experience of HSCT in a cohort of five patients with HIGM I syndrome.…”
mentioning
confidence: 99%
“…RIC regimens are associated with less toxicity and may be an alternative option for nonmalignant disease, particularly for those who already have several complications (7,(17)(18)(19)(20). However, for CGD patients who have normal immunity except for oxidative killing and have never received myelosuppressive chemotherapy, the RIC regimen which we used at the first transplantation would not be sufficient to establish enough donor chimerism after haploidentical BMT.…”
Section: Discussionmentioning
confidence: 99%